1995
DOI: 10.1002/j.1460-2075.1995.tb07207.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a theta-class glutathione transferase.

Abstract: Glutathione S‐transferases (GSTs) are a family of enzymes involved in the cellular detoxification of xenotoxins. Cytosolic GSTs have been grouped into four evolutionary classes for which there are representative crystal structures of three of them. Here we report the first crystal structure of a theta‐class GST. So far, all available GST crystal structures suggest that a strictly conserved tyrosine near the N‐terminus plays a critical role in the reaction mechanism and such a role has been convincingly demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
226
1
4

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 48 publications
4
226
1
4
Order By: Relevance
“…In addition, agGST1-2 possesses a serine residue near the N terminus (Ser-10) and an asparagine (Asn-48) (shown in bold in Fig. 5) near the invariant proline, both of which are characteristics of insect class I GSTs (22).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, agGST1-2 possesses a serine residue near the N terminus (Ser-10) and an asparagine (Asn-48) (shown in bold in Fig. 5) near the invariant proline, both of which are characteristics of insect class I GSTs (22).…”
Section: Resultsmentioning
confidence: 99%
“…Site-directed mutagenesis studies of the -GST from the Australian sheep blowfly (Lucilia cuprina) and the -GST from the bacterium Methylophilus sp. strain DM11 indicated that the Ser-9 and Ser-12 residues, respectively, are essential for enzyme activity (Board et al, 1995;Vuilleumier and Leisinger, 1996). Furthermore, the three-dimensional structure of a -GST from L. cuprina showed that Ser-9 occupies a position close to that of the catalytically important Tyr of mammalian ␣-, -, and -GSTs (Wilce et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…strain DM11 indicated that the Ser-9 and Ser-12 residues, respectively, are essential for enzyme activity (Board et al, 1995;Vuilleumier and Leisinger, 1996). Furthermore, the three-dimensional structure of a -GST from L. cuprina showed that Ser-9 occupies a position close to that of the catalytically important Tyr of mammalian ␣-, -, and -GSTs (Wilce et al, 1995). Recently, the first three-dimensional structure of a plant GST was reported (Reinemer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of a Theta-class GST from Lucilia cuprina revealed that the insect GST has a deeper active site than mammalian GSTs. Furthermore, amino acid sequence alignment has suggested that the extended α-helix 5 in the mammalian Theta-class isoenzymes would result in an even deeper active site in these enzymes [26]. Because of the apparent increased affinity of GSTT2-2 for substrates with increased carbon chain length, and the inability of GSTT2-2 to bind to conventional glutathione\agarose affinity matrices, we attempted to purify GSTT2-2 using a GSH-agarose matrix with a very long spacer arm, equivalent to 20 carbon atoms.…”
Section: Figure 5 Ph Profile Of Gstt2-2 With Cumene Hydroperoxide As mentioning
confidence: 99%